PENGARUH STANDAR PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN DI PUSKESMAS NANGA PINOH KABUPATEN MELAWI - Maya Dwi Ranti E.42008028 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This essay aims at finding out if the influence of the standard of care for patients at the health center level of satisfaction Nanga Pinoh Melawi regency. This study was conducted based on the problemsthat occur in the health center Nanga pinoh associated with the level of patient satisfaction andservice standards are among the factors that influence the level of satisfaction of the patient's own.This research was conducted using quantitative paradigm with methods associative / causalrelationship. The hypothesis formulated in this research that there is a positive effect between thelevel of service standards for patient satisfaction. As for the samples in the study of patients on onetype of service that Public Poli at Nanga Pinoh Melawi health center. The result using the correlationproduct momentwith significance level (?) of 5% is known that the standard of care affect the levelof patient satisfaction was 0.388. The results of the calculation of the coefficient of determination isknown that the effect of the standard of care for patients at the health center level of satisfactionNanga Pinoh by 15.1% while the remaining 84.9% is influenced by other variables not examined inthis study. Keyword : Service Standards and Patient Satisfaction.